Phytochemical Screening, Antioxidant, and Inhibition Activity of Against α-Amylase and α-Glucosidase - Jaweria Nisar; Syed Muhammad A. Shah; Muhammad Akram; Sultan Ayaz; Abid Rashid (SAGE Publishing, 2022)
Picrorhiza kurroa (P.K) usually familiar as kutki is a well-known plant in the Ayurvedic system of medicine due to its reported activities including antidiabetic, antibacterial, antioxidant, antitumor, anti-inflammatory, and hepatoprotective. The current research was intended to evaluate the antioxidant, inhibition activity of the ethanolic, methanolic, and aqueous extracts of P.K roots against α-amylase and α-glucosidase in vitro, after the phytochemical analysis . For this purpose, P.K roots were extracted with ethanol (EthPk), methanol (MthPk), and distilled water (AqPk) and phytochemical study of the extracts were performed to recognize the total phenolic content (TPC) and total flavonoids content (TFC). Antioxidant capability of the extracts was assessed by FRAP, ABTS, and DPPH assay. α-amylase inhibitory and α-glucosidase inhibitory activities were also determined. Software SPSS-23 was used to statistically analyze with One Way ANOVA and results were stated as mean standard deviation. Result of the study showed that MthPk contained the maximum concentration of TPC and TFC than EthPk and AqEh. Antioxidants in terms of DPPH (lowest IC 50 = .894 ± .57), FRAP (612.54 ± 11.73) and ABTS (406.42 ± 4.02) assay was also maximum in MthPk. MthPk was also showed maximum inhibition activity against α-amylase and α-glucosidase with lowest IC 50 (.39 ± .41; .61 ± .24), respectively. The extracts α-amylase and α-glucosidase inhibitory activities order was as MthPk > EthPk> AqPk. Results clearly specified that the methanolic extract of Picrorhiza kurroa have the maximum antioxidant, α-amylase, and α-glucosidase inhibitory activities. A positive correlation of TPC, TFC with antioxidant, and α-amylase and α-glucosidase inhibition activities of the P.K roots were also shown. The plant has capability to diminish the oxidative stress and can be used to treat diabetes by inhibiting α-amylase and α-glucosidase actions.